“Propuesta para el desarrollo de software educativo lúdico basada en el diseño universal para el aprendizaje” - Brito Casanova, Geovanny José (2022)
The purpose of this study is mainly directed to software developers, especially to those who are looking for how to aim their educational applications to personalization and digital inclusion. Thus, this study proposes to adapt the current model of Universal Design for Learning (UDL), focusing on the development of playful educational software, deepening in a literature review based on the verification points of each principle, in order to determine and select the most suitable for the development of playful educational software. These were validated by means of surveys, to later demonstrate the proposal by means of a software